2015
DOI: 10.1073/pnas.1508514112
|View full text |Cite
|
Sign up to set email alerts
|

p27 kip1 controls H-Ras/MAPK activation and cell cycle entry via modulation of MT stability

Abstract: The cyclin-dependent kinase (CDK) inhibitor p27 kip1 is a critical regulator of the G1/S-phase transition of the cell cycle and also regulates microtubule (MT) stability. This latter function is exerted by modulating the activity of stathmin, an MT-destabilizing protein, and by direct binding to MTs. We recently demonstrated that increased proliferation in p27 kip1 -null mice is reverted by concomitant deletion of stathmin in p27 kip1 /stathmin double-KO mice, suggesting that a CDK-independent function of p27 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 43 publications
4
59
0
Order By: Relevance
“…Our experiment revealed that SPOCK1 enhances the activity of the PI3K/Akt pathway, a crucial signaling pathway that promotes cell proliferation, 17 induces the EMT, [18][19][20] and attenuates cell apoptosis by stimulating the Bax-mediated signaling pathway. [21][22][23] Our observations showed that inactivation of the PI3K/Akt pathway through the downregulation of SPOCK1 is associated with cell apoptosis due to subsequent activation of the caspase-9/caspase-3/PARP pathway. On the basis of the role of SPOCK1 in cell proliferation, migration, invasion, and EMT, we hypothesize that SPOCK1 exerts its antiapoptotic and oncogenic effects through the PI3K/Akt pathway.…”
Section: Discussionmentioning
confidence: 62%
“…Our experiment revealed that SPOCK1 enhances the activity of the PI3K/Akt pathway, a crucial signaling pathway that promotes cell proliferation, 17 induces the EMT, [18][19][20] and attenuates cell apoptosis by stimulating the Bax-mediated signaling pathway. [21][22][23] Our observations showed that inactivation of the PI3K/Akt pathway through the downregulation of SPOCK1 is associated with cell apoptosis due to subsequent activation of the caspase-9/caspase-3/PARP pathway. On the basis of the role of SPOCK1 in cell proliferation, migration, invasion, and EMT, we hypothesize that SPOCK1 exerts its antiapoptotic and oncogenic effects through the PI3K/Akt pathway.…”
Section: Discussionmentioning
confidence: 62%
“…Previous reports show stathmin is negatively controlled by the cell cycle inhibitor p27 . Therefore, we assessed the expression of p27 in the PHAP1‐modulated cells.…”
Section: Resultsmentioning
confidence: 98%
“…regulating Akt/p27/stathmin pathway Previous reports show stathmin is negatively controlled by the cell cycle inhibitor p27. 20 Therefore, we assessed the expression of p27 in the PHAP1-modulated cells. As expected, the upstream negative regulator p27 was increased in PHAP1 down-regulated U251 and U87 cells, whereas decreased in PHAP1 overexpressed U251 and U87 cells ( Figure 4A,B).…”
Section: Phap1 Promotes Glioma Cell Proliferation Bymentioning
confidence: 99%
“…Extraction of total proteins, Western blot, and immunoprecipitations analyses were performed as described (Sonego et al , ; Fabris et al , ; Lovisa et al , ). Primary antibodies used were as follows: vinculin (N‐19, 1:1,000), CDK6 (C‐21, sc‐177, 1:800), CDK4 (C‐22, sc‐260, 1:400), pRB1S780 (sc‐12901, 1:400), PSF (39‐1, sc‐101137, 1:800), CHK1 (G‐4, sc‐8408, 1:500), luciferase (sc‐32896), lamin A (C‐20 sc‐6214) (Santa Cruz Biotechnology); FOXO3 (75D8, #2497, 1:600), cyclin D3 (DCS22, #2936, 1:500), pCHK1S296 (#2349, 1:500), H2AX (D17A3, #7631, 1:500), ATR (#2790, 1:500), ATM (#2873, 1:500), and cleaved caspase‐3 Asp175 (#9661, 1:500) (Cell Signaling); cyclin D1 (DCS‐6, CC12, 1:1,000) (Millipore); γH2AXS139 (#2577, 1:500) (Upstate Biotechnology); RB1 (554136, 1:500) and GRB2 (610111, 1:300) (BD Biosciences); actin (A5060, 1:500), tubulin (T5168, 1:1,000), Flag (F3040), OP18 (O0138, 1:1,000), and V5 (A7345)‐ and HA (A2095)‐agarose conjugated (Sigma‐Aldrich Co); GFP (11 814 440 001, 1:500) (Roche); Ki67 (ab15580, 1:1,000) (Abcam).…”
Section: Methodsmentioning
confidence: 99%
“…qRT–PCR analyses were performed essentially as described (Sonego et al , ; Berton et al , ; Fabris et al , ). Briefly, total RNA was extracted using SV 96 Total RNA Isolation System kit (Promega) or Trizol reagent (Invitrogen), quantified using NanoDrop (Thermo Fisher Scientific Inc., USA), and retro‐transcribed using the Go‐Script reverse transcriptase (Promega) or the AMV reverse transcriptase (Promega).…”
Section: Methodsmentioning
confidence: 99%